MORPHOLOGICAL CHANGES IN THE ULTRASTRUCTURE OF THE GASTRIC MUCOSA IN THE LATE STAGES OF HYPOTHYROIDISM - Bezshtanko, N.A.; Khashchyna, T.V. (World of Medicine and Biology, 2024)
The ultrastructure of rat gastric mucosa was studied by electron microscopic examination on days 50, 100, and 150 after thyroidectomy. It was established that as hypothyroidism develops, dystrophic-destructive changes become pronounced in chief and parietal cells on days 50 and 100, while the latter is combined with compensatory changes in mucous cells. Endocrine cells are more resistant to the lack of thyroid hormones. On day 150, destructive and dystrophic changes predominate in all structural components of mucous cells, and decompensation comes to the fore.